Edukasi Pola Asuh Positif Untuk Mendukung Perkembangan Balita Di Wilayah Kerja Puskesmas Maros: Edukasi Pola Asuh Positif Untuk Mendukung Perkembangan Balita Di Wilayah Kerja Puskesmas Maros - Marina Marina (Sekolah Tinggi Ilmu Kesehatan Gunung Sari, 2025)
Parenting plays a crucial role in supporting optimal toddler development, encompassing physical, cognitive, language, emotional, and social aspects. Parents' lack of understanding of positive parenting remains a community issue and can hinder toddler development. This community service initiative aims to improve parents' knowledge and understanding of positive parenting in supporting toddler development in the Maros Community Health Center (Puskesmas) area. The implementation method includes education through health counseling, interactive discussions, and participant understanding evaluation. The target group is parents of toddlers. The results indicate an increase in parental knowledge regarding the concept of positive parenting, the importance of age-appropriate developmental stimulation, and the role of parents in creating a responsive and loving care environment. This initiative was concluded to be effective in improving parental understanding and is expected to support optimal toddler development